Implementasi Kebijakan Penanggulangan Kemiskinan di Kawasan Perkotaan - Zulkarnaini ' (Universitas Riau, 2011)
This study examines the policy implementation to reduce poverty in urban areas with the object ofstudy Pekanbaru City. The focus of research directed at the implementation of the Program PemberdayaanKelurahan (PPK) in the form of Usaha Ekonomi Kelurahan-Simpan Pinjam (UEK-SP) to answer the questionwhy this program has not been able to accomplished with a maximum in the city of Pekanbaru. It is seen from11 regencies / cities in Riau Province, Pekanbaru is a region of low absorption of funds including loans UEK-SP. This study aims to get clear information and identify the factors that influence the implementation processof poverty reduction through the PPK in Pekanbaru City